Survival of Listeria monocytogenes in frozen burger patties - Wong, Woan Chwen (2011)
Listeria monocytogenes is a foodborne pathogen which has caused outbreaks in several nations in which processed meats were the vehicle. The purpose of this study were to determine the prevalence of L. monocytogenes from frozen burger patties, assess the characteristics of the L. monocytogenes strains isolated from burger patties, and determine the effect of different cooking time in decontamination of L. monocytogenes in chicken burger patties. A total of 220 samples were purchased from hypermarkets and retail shops in Malaysia from June to October 2009. Prevalence of L. monocytogenes in burger patties from this study was found to be 15.9%, in which the prevalence of L. monocytogenes in meat-based burger patties (22.3%) is significantly higher than vegetarian burger patties (9.3%) at P<0.05. L. monocytogenes was found to be most frequently detected in chicken patties (33.3%), followed by beef patties (22.9%), and fish patties (10.5%). By using MPN-PCR method, 15.9% of the samples were found to be positive for L. monocytogenes. MPN plating and direct plating method can only detected 7.7% and 7.3%, respectively. The density of L. monocytogenes detected in burger patties was ranged from 0 to 1,100 MPN/g. Forty-one isolates of L. monocytogenes recovered from raw burger patties were characterized based on their antibiotic resistance and RAPD banding pattern. In particular, 31.7% of isolates were susceptible to 11 antibiotics tested. Result showed that, resistance to tetracycline was most common (46.3%), followed by erythromycin (36.6%), amikacin (31.7%), and SMZTMP (17.1%). All L. monocytogenes strains were sensitive towards imipenem and gentamicin. On the other hand, 31 out of 41 isolates in current study were typabled by RAPD-PCR with primer OPA 10. As observed from the dendrogram, these L. monocytogenes strains were classified into 3 clusters. These clusters were occupied by the strains recovered from all types of burger patties. A simulation study was conducted to determine sufficient cooking time to reduce the number of L. monocytogenes present in chicken burger patties to safe level which is fit for human consumption. Artificially contaminated burger patties were cooked for 0, 2, 4, 5, 8, and 10 min to determine survival of L. monocytogenes. Results demonstrated a linear correlation (R2 = 0.87)between mean log reduction of L. monocytogenes and cooking time. As a result from this study, it is suggested that a cooking time of 6 min or more is sufficient to decontaminate the burger patties, without control of temperatures of internal burger patties and cooking environment